Assessment of surface water quality using statistical analysis methods: Orontes River (Case study) - Lina Khouri; Muhammad Bashar Al-Mufti (مجلة بغداد للعلوم)
The study investigates the water quality of the Orontes River, which is considered one of the important water recourses in Syria, as it is used for drinking, irrigation, swimming and industrial needs. A database of 660 measurements for 13 parameters concentrations used, were taken from 11 monitoring points distributed along the Orontes River for a period of five years from 2015-2019, and to study the correlation between parameters and their impact on water quality, statistical analysis was applied using (SPSS) program. Cluster analysis was applied in order to classify the pollution areas along the river, and two groups were given: (low pollution - high pollution), where the areas were classified according to the sources of pollution to which they are exposed. This indicates the importance of cluster analysis in studying movement of the pollutants and reducing the number of sampling points. Factor analysis gave 5 main factors responsible for explaining 92.86% of the total variance, with 78.2% measurement quality, it includes 7 basic parameters: (EC, TUR, NO3, Na, pH, NH4, COD). This study showed the ability of factor analysis in determining the most important parameters that effect on the water quality, which helps in reducing the number of parameters needed for sampling.